2008
DOI: 10.1101/gad.1718108
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of trophoblast stem cells into giant cells is triggered by p57/Kip2 inhibition of CDK1 activity

Abstract: Genome endoreduplication during mammalian development is a rare event for which the mechanism is unknown. It first appears when fibroblast growth factor 4 (FGF4) deprivation induces differentiation of trophoblast stem (TS) cells into the nonproliferating trophoblast giant (TG) cells required for embryo implantation. Here we show that RO3306 inhibition of cyclin-dependent protein kinase 1 (CDK1), the enzyme required to enter mitosis, induced differentiation of TS cells into TG cells. In contrast, RO3306 induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
280
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(306 citation statements)
references
References 60 publications
22
280
1
3
Order By: Relevance
“…Inhibition of Cdk1 activity via mutagenesis (28,31) or selective drug inhibitors (26) has been shown to result in increased endoreduplication. Corroborating this hypothesis, p57-mediated inhibition of Cdk1 activity in an endogenous system, trophoblast giant cells, has been shown to be essential for repeated rounds of endoreduplication that take place during their maturation (32); in the same system, the authors have also shown that Cdk2 is required for endoreduplication.…”
Section: Discussionmentioning
confidence: 88%
“…Inhibition of Cdk1 activity via mutagenesis (28,31) or selective drug inhibitors (26) has been shown to result in increased endoreduplication. Corroborating this hypothesis, p57-mediated inhibition of Cdk1 activity in an endogenous system, trophoblast giant cells, has been shown to be essential for repeated rounds of endoreduplication that take place during their maturation (32); in the same system, the authors have also shown that Cdk2 is required for endoreduplication.…”
Section: Discussionmentioning
confidence: 88%
“…In particular, CKI is able to stabilize MyoD, a transcription factor that is highly specific for muscle involved in myogenic differentiation. p57 Kip2 is also involved in the differentiation of several other cell phenotypes, including podocytes (79), placental cells (65,80,81), keratinocytes (82), pancreatic cells (83), hepatocytes (84,85), T-lymphocytes (86), spermatozoa (87,88), Leydig cells (88), chondrocytes (89)(90)(91), and adrenal cortex cells (92).…”
Section: P57 Kip2 Metabolismmentioning
confidence: 99%
“…Moreover, coordinated changes of p57 Kip2 , p27 Kip1 , and p21 Cip1 have been shown clearly during keratinocyte maturation (76) and human placenta development (65,80,81).…”
Section: P57 Kip2 Metabolismmentioning
confidence: 99%
“…Other highly expressed genes included scavenger receptor class B, member 1 (Scarb 1), required for the phagocytic activity of TGCs (38,39), and the Cdk1 inhibitor p57 (Cdkn1c), required for TGC endoreplication (22). We analyzed the E9.5 TGC mRNA-Seq profile with the GOrilla gene ontology (GO) tool (http://www.ncbi.nim.nih.gov/pubmed/ 19192299), which uses an algorithm that precludes the choice of an arbitrary P value cutoff.…”
Section: Sg Cghmentioning
confidence: 99%
“…Mouse TGCs can be differentiated in culture from trophoblast stem cells by the absence of fibroblast growth factor 4, and a rat trophoblast cell culture line exists that becomes polyploid in culture, attaining up to 64C ploidy (19,20). Analysis of these models revealed that the cyclindependent kinase (CDK) inhibitor p57 is necessary for the onset of the endocycle (21,22). Differential DNA replication, however, was not examined in these cell culture models.…”
mentioning
confidence: 99%